Logistics for cool transportation and preservation of fruits and vegetables - Yamauchi, Futoshi (CGIAR System Organization, 2024)
A refrigeration-equipped truck transports fruits and vegetables in standardized plastic crates. The efficient operation of cool transportation also needs a logistical support system. Cool transportation can preserve the quality of fruits and vegetables when transporting them in distance from production sites, typically in the northern regions, to large demand centers in the southern regions. Post-harvest losses in quality and quantity are reduced to a minimum to benefit producers and consumers, often spatially distanced. Preserving product quality is expected to increase incentives to enhance product quality